2014
DOI: 10.3109/10717544.2014.948644
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of buccal films impregnated with selegiline-loaded nanospheres

Abstract: Poor peroral therapeutic efficiency of selegiline is primarily due to the extensive hepatic metabolism and hence the need for an alternative route of administration. The present study is based on evaluation of a buccal film which is impregnated with selegiline nanospheres to enhance the systemic bioavailability. Selegiline-loaded nanospheres prepared using poly(lactide-co-glycolide) was embedded into buccal films (F 1 -F 4 ) with varying polymer composition [hydroxypropyl methylcellulose and eudragit]. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…A mucoadhesive drug delivery system provides various advantages by targeting and localizing the nanoparticles at a target site, by decreasing variation in drug level in the plasma, and by extending residence time at the confined target site of drug penetration, and thereby reducing side effects [5][6][7]. Nanoparticles offer promising drug delivery technology by improving the therapeutic window and increasing their tolerability and enhancing their efficacy in the body.…”
Section: Introductionmentioning
confidence: 99%
“…A mucoadhesive drug delivery system provides various advantages by targeting and localizing the nanoparticles at a target site, by decreasing variation in drug level in the plasma, and by extending residence time at the confined target site of drug penetration, and thereby reducing side effects [5][6][7]. Nanoparticles offer promising drug delivery technology by improving the therapeutic window and increasing their tolerability and enhancing their efficacy in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the combination of carbopol 974P and HPMC K100 provides adequate swelling and mucoadhesive strength to the film. 15,18,26 Different combinations of these three polymers were mixed to form films of varying composition (named Z1-Z4). Previous literature notes that these polymers are capable of controlling the release of pharmaceutically active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The solution was then centrifuged at 10,000 rpm for 2 min, then the supernatant was filtered and analyzed by HPLC. 15 …”
Section: Drug Contentmentioning
confidence: 99%
“…The EE of drug is mainly dictated by the partition coefficient of the drug and its inherent solubility in the specific polymer. However, the solubility of drug in polymer is normally influenced by the physicochemical properties (molecular weight and chemical nature of drug and polymer) as well as the probable drug-polymer interaction [31]. The effect of polymer concentration (40-200 mg) on the %EE and %DL values were assessed and are depicted in Table 1.…”
Section: Characterization Of Gemcitabine Nanoparticlesmentioning
confidence: 99%